Design of SIW-based antenna-filter for 6.2 GHz applications / Muhammad Syamil Omar - Omar, Muhammad Syamil (2014)
In this paper a design of integrated antenna and filter was proposed. The design is based on Substrate Integrated Waveguide (SIW) on a Rogers 3003 substrate fabricated by printed circuit board technique. The dielectric constant of the substrate for both filter and antenna is sr = 3. The filter and antenna is designed and fabricated with 0.75 mm and 0.5 mm substrate height respectively. At first, the circular SIW filter on the TMoio was designed separately before integrating with a circular microstrip antenna operating on TMno. At 6.2 GHz resonance frequency, a good simulation results are obtained with 6.6 dB gain and return loss less than -10 dB. Then, the simulated design is fabricated and measured. The result of the simulation is then compared with the measurement. The design is capable to reduce the size of receiving system and lowering the overall fabrication cost since it does not required a matching circuit.